Mineralogical and elemental analysis of Kazakh coals from three mines: Preliminary insights from mode of occurrence to environmental impacts - Medet Junussov; Farkhad Tarikhov; Abaidildin Abildakhanov; Dauren Zhanaidar; Gulnur Mekenbek; Aizada Assambayeva (Walter de Gruyter GmbH, 2024)
This study aims to comprehensively characterize coal extracted from three active mines in northeastern Kazakhstan: Lenin, Saradyr, and Bogatyr. These mines exploit two Carboniferous coal-bearing formations, Dolyn and Karagandy. Dolyn, extracted by the Lenin underground mine at a depth of 700 m, contrasts with Karagandy, extracted at depths up to 260 m in Saradyr and Bogatyr. Six selected samples from the Lenin, Saradyr, and Bogatyr mines underwent various analyses, including proximate and ultimate analyses, elemental analyses (acid digestions with HCl + HNO 3 + HF, ICP-MS), and determination of mineral matter contents (XRD and SEM-EDS). This research aimed to understand the mode of occurrence of minerals and elements, technological and environmental implications of the coal seams extracted from these mines. Results indicate low sulfur and high ash content in the organic matter of all samples. Quartz and kaolinite dominate, with minor euhedral pyrite present in all samples. Framboidal pyrite, iron oxides, and rare earth element (REE)-bearing minerals are exclusively found in Saradyr and Bogatyr samples. Quartz and kaolinite likely reached the peat swamp through detrital processes, while pyrite formation occurred through both syngenetic and epigenetic processes in the coal samples. Ratios like Ce n /Ce n , Eu n /Eu n , Y n /Ho n , and Gd n /Gd n suggest REE deposition in anoxic hydrothermal water environments, possibly indicating a tuffaceous origin for the coal samples. Examining the elements’ mode of occurrence suggests their preferential association with mineral matter. Strong positive correlations among elements like Al, K, Na, Ti, Ba, Be, Ni, Cr, Co, Ga, Sc, V, As, Pb, Cu, Zn, and Zr, along with Eu and Sc of the REEs, suggest association with ash yield, consistent with kaolinite and accessory minerals. Comparative analysis of inorganic geochemical composition of coal worldwide reveals notable depletion of major, trace elements, and REEs in samples from all three mines, suggesting limited economic interest. Furthermore, coal samples containing trace elements pose minimal environmental impact.
Keywords: Kazakh; Mining engineering; Geology; Coal mining; Mode (computer interface); Geochemistry; Environmental science; Mineralogy; Archaeology; Earth science; Coal; Geography; Computer science; Philosophy; Linguistics; Operating system; type of access: open access